Family history and risk assessment in black South African women with breast cancer - Wainstein, Tasha (My University, 2012)
Black South African women who have breast cancer have been found in general to be diagnosed at a younger age, have a more aggressive disease and a poorer prognosis in comparison to their Caucasian counterparts. However, there is a paucity of research related to the manner in which breast cancer is inherited in black South African families. It is also not known whether these individuals harbour deleterious mutations in breast cancer predisposition genes. As 5-10% of breast cancers have been shown to be inherited, in white populations, this study aimed to investigate family history and inheritance of breast cancer in black South African women. It also aimed to evaluate the use and consistency of existing risk assessment models in this population. A retrospective, file-based analysis of 45 black South African women who were diagnosed with breast cancer before the age of 50 years was performed. The probands were ascertained from the Genetic Counselling Clinic held weekly at the Breast and Plastic Clinic, Chris Hani Baragwanath Hospital. Information was obtained from the subjects’ genetic counselling files as well as the Oncology database that is housed at the Clinic. Information pertaining to the personal breast disease history of the probands as well as their family histories (three generation pedigrees) was entered into a spreadsheet and analysed. The results of this study indicated that there were very few young black South African women with breast cancer who had a significant family history of cancer (4/45; 9%). Family history is an important factor in assessing an individual’s breast cancer risks. Results also suggested that age at diagnosis may not be an appropriate predictor of inherited breast cancer risk in this population. A significant proportion of black South African women diagnosed with breast cancer younger than 50 years might be proven to have sporadic rather than inherited breast cancers. Three risk assessment tools (The Claus Model, the Tyrer-Cuzick Model and the Manchester Scoring system) were evaluated in this study. They were shown to have some degree of consistency and each had unique advantages and disadvantages of use within this population. The main limitation of these risk assessment tools is that they were designed based on data from Caucasian populations and as such their applicability to a non-Caucasian population has not been validated. Their true validity within this population can only be established once molecular genetic analysis has been performed. This study highlights the necessity of molecular genetic screening in this population in order to further delineate which individuals in this population are truly at an increased risk of developing inherited breast cancer. This information is important because it can inform which individuals would benefit from cancer risk assessments and various cancer prevention and reduction strategies. Information obtained from this study will be useful to direct future research in this population with respect to genetic counselling for inherited breast cancer.
Keywords: Genetic Counseling